(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the value of the Sliding sign in diagnosing uterine-abdominal wall adhesions in pregnant women with previous cesarean section scars. Methods: A cross-sectional descriptive study was conducted on 130 pregnant women with a history of cesarean section undergoing elective surgery at Hanoi Obstetrics and Gynecology Hospital from September to November 2025. All participants underwent preoperative ultrasound to evaluate the sliding sign, which was then compared with intraoperative findings. Results: The overall prevalence of uterine-abdominal wall adhesions was 54.6%, with moderate to severe adhesions accounting for 34.6%. A negative sliding sign was significantly associated with grade 2-3 adhesions (75.6%), with an OR of 40.7 (95% CI: 13.9-119.0; p < 0.001). The diagnostic values of the sliding sign were: sensitivity 75.6%, specificity 92.9%, positive predictive value 85.0%, negative predictive value 87.8%. Both the delivery time and total operative time were significantly prolonged in the negative sliding sign group (p < 0.001). Clinically, a depressed scar was strongly associated with high-grade adhesions (p = 0.001). Conclusion: The sliding sign is a simple yet highly reliable ultrasound marker for predicting uterine-abdominal wall adhesions in women with previous cesarean sections. Its routine application can assist in surgical planning, reduce the risk of complications, and improve patient safety.